Chemical Analysis of Wastewater Produced in an Industrial Enterprise - Karimova Feruza Sattarovna; Jo`rayeva Umida Boxodirovna; Jumaboyev Olim Sharofovich (Genius Publishing Group, 2023)
In this article, the chemical composition of wastewater produced in industrial enterprises, in particular, the composition of wastewater produced in the process of obtaining ultramarine pigment produced at the joint venture "Sofitel" LLC located in the industrial area of Jizzakh city, was studied using the mass spectrometry method. results are reported.
Keywords: Wastewater; mass spectrometry; adsorbent; processing